Pengaruh Padat Tebar Terhadap Pertumbuhan Ikan Nila (Oreochromis niloticus) Pada Sistem Akuaponik Teknik Aliran Film Nutrisi (NFT) - Margareth Yuni Wati Ragho; Ridwan Tobuku; Asriati Djonu (Jurnal Aquatik, 2026)
This study aims to determine the effect of stocking density on the growth of tilapia (Oreochromis niloticus) cultivated in an aquaponic system using the Nutrient Film Flow (NFT) technique. The study was carried out with four different stocking densities, namely 15, 20, 25, and 30 fish per unit of aquaponic system. The method used was an experiment with a Complete Random Design (RAL) design consisting of 3 replicas. The data obtained was analyzed using multiple fingerprint analysis (ANOVA) with a 95% confidence interval. The results showed that stocking density had a significant effect on tilapia growth, where treatment with a stocking density of 15 fish showed the best growth, followed by treatment of 20 fish, while higher stocking density (25 and 30 fish) reduced the growth rate of fish. In conclusion, the optimal stocking density for tilapia growth in an NFT aquaponics system is 15 to 20 fish per unit of the system. This study provides recommendations for tilapia farmers in aquaponic systems in order to be able to manage stocking density properly to support optimal growth. Keywords: Stocking density, Tilapia, Aquaponics, Nutrient Film Flow (NFT) Technique, Fish growth.